Sugar sweetened beverages, natural fruit juices, and cancer: what we know and what still needs to be assessed - Eshaghian, Niloofar; Zare, Mohammad Javad; Mohammadian, Mohammad Keshavarz; Gozidehkar, Zohre; Ahansaz, Afsaneh; Askari, Gholamreza; Asadi, Masoomeh; Milajerdi, Alireza; Sadeghi, Omid (Frontiers in Nutrition, 2023)
Cancer is known as one of the leading causes of death in the world. In addition to early mortality, cancer is associated with disability in affected patients. Among environmental risk factors, special attention has been paid to the role of dietary factors. In recent decades, the consumption of sugar-sweetened beverages (SSBs) and natural fruit juices has increased.Several studies have assessed the effects of these beverages on human health and found that a higher intake of SSBs is associated with a greater risk of obesity, diabetes, cardiovascular diseases, hypertension, and non-alcoholic fatty liver disease. However, current evidence for cancer incidence and mortality is not conclusive. In the current review, we concluded that SSBs intake might be positively associated with cancer incidence/mortality through their increasing effects on obesity, inflammatory biomarkers, serum levels of insulin-like growth factor-I (IGF-I), and advanced glycation end-products. Such a positive association was also seen for natural fruit juices. However, types of natural fruit juices were not considered in most previous studies.In addition, some types of cancer including brain, lung, and renal cancers were not assessed in relation to SSBs and natural fruit juices. Therefore, further studies are needed in this regard.